INTEGRASI TEKNOLOGI DALAM MANAJEMEN PENDIDIKAN ISLAM: MENINGKATKAN KINERJA GURU DI ERA DIGITAL - Muh Ibnu Sholeh; Nur Efendi (Institute Agama Islam Al-Qolam Malang, 2023)
This study aims to find out how to use technology to improve teacher performance in the digital era, what are the challenges of its implementation and what are the steps for implementing technology in Islamic education management to improve teacher performance in the digital era. The method used in this research is library research method. Collecting data by looking for sources from various sources such as books, journals, and existing research. The data obtained from the literature study were analyzed using an interactive qualitative model. This data analysis model consists of data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that the use of technology to improve teacher performance through e-learning and blended learning in Islamic education. The use of Islamic education applications in classroom management by means of scheduling applications, task management applications, learning material applications, quiz and evaluation applications and communication applications. Teacher professional training and development through technology by means of independent learning, webinars and virtual conferences, collaboration and networking, use of learning tools and applications, online certification programs and building digital portfolios. The challenges faced in integrating technology in Islamic education include the digital divide, attention to religious values, professional training and development, data security and privacy, and content and quality management. The steps for implementing technology in Islamic education management are through analyzing technology needs, training and developing teachers, forming educational technology teams, planning technology-based learning, using applications and supporting platforms, monitoring and evaluation and continuity and sustainable development.